2015
DOI: 10.5694/mja15.00189
|View full text |Cite
|
Sign up to set email alerts
|

“Teaching by humiliation” and mistreatment of medical students in clinical rotations: a pilot study

Abstract: Objective: To generate a contemporary understanding of “teaching by humiliation” as experienced by medical students in Australia. Design, setting and participants: In this pilot study, we surveyed final‐stage medical students from two Australian medical schools about their experiences of teaching by humiliation during their adult and paediatric clinical rotations. The students were invited to complete the anonymous survey at the end of their paediatric rotation in Semester 2 of 2013. We used descriptive statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 25 publications
(67 reference statements)
8
64
0
2
Order By: Relevance
“…This is consistent with the increasing recognition in medical education of the effects of emotions on learning and the new understanding of emotional intelligence ready for application in our field . Our study emphasises the importance of providing individualised affective support in preference to dismissing struggling students as soft, spoilt and needing to ‘toughen up’ (or assuming they will take up a specialty that does not require patient contact).…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with the increasing recognition in medical education of the effects of emotions on learning and the new understanding of emotional intelligence ready for application in our field . Our study emphasises the importance of providing individualised affective support in preference to dismissing struggling students as soft, spoilt and needing to ‘toughen up’ (or assuming they will take up a specialty that does not require patient contact).…”
Section: Discussionsupporting
confidence: 86%
“…Although a multipronged approach is needed to generate systemic change,3 this pilot offers a uniquely positive, creative approach. It aims to enable students, the most vulnerable in the medical hierarchy, to begin to develop acting and leadership skills that will help them deal with challenges in the clinical setting, including mistreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent American research found 59.4% of trainees experienced harassment or discrimination during medical school 2. Research at two Australian medical schools found 74.0% of students experienced ‘teaching by humiliation’ and 83.1% witnessed it 3. Some students and teachers believe coping with humiliation is part of professional development 2.…”
Section: Introductionmentioning
confidence: 99%
“…19 Traditionally, handover has been seen as a tool to improve the training experience. 21 This educational combination still leaves its mark on many overnight-to-day handovers, and can be one of the less desirable and sometimes anxiety provoking aspects of night shift. 21 This educational combination still leaves its mark on many overnight-to-day handovers, and can be one of the less desirable and sometimes anxiety provoking aspects of night shift.…”
Section: Training Experience On Night Shiftmentioning
confidence: 99%
“…20 Such tradition has also seen the use of intimidation to enhance learning and may involve questioning the decision-making that occurred, the disposition or management plan that has been proposed, or the anatomical or physiological rationale for various management options. 21 This educational combination still leaves its mark on many overnight-to-day handovers, and can be one of the less desirable and sometimes anxiety provoking aspects of night shift. At best, this can give the night registrar a chance to eloquently display their medical expertise.…”
Section: Training Experience On Night Shiftmentioning
confidence: 99%